Model of History Education Laboratory Management - Tarunasena Tarunasena; Ayi Budi Santosa; Iing Yulianti (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2020)
The background of this research is based on the importance of forming professionalhistory teacher candidates in accordance with the above mentioned expectations,the Department of Historical Education needs to empower and develop the HistoryLaboratory as a superior program. The History Education Laboratory is centered onthe field of science, a place of authority and academic integrity. The HistoryEducation Laboratory was formed in order to meet the needs of the department andthe development of academics. The main limitation of this research problem is